The Contribution of Science, Technology, and the Arts to the Development of Christian Educators’ Creative and Innovative Competencies within the Framework of the Great Commission - Chanita Christie (Sekolah Tinggi Teologia Kerusso Indonesia, 2025)
With the rampant and rapid development of technology in the digital era, there is a change in character and the development of professional skills in society. Where this affects the ethics and behavior of today's younger generation, this research was conducted out of an urgent need to analyze the impact of Christian Religious Education in balancing technological mastery with a strong moral foundation. The purpose of this study is to understand how Christian religious education can shape students' character, such as honesty, responsibility, and ethics, as well as develop professional skills needed in the digital workplace. This research uses a qualitative methodology with a case study approach, where data is collected through in-depth interviews, observations, and document analysis from several Christian education institutions. How Christian values are integrated into the learning process to shape a better personality, and how students can develop digital skills and soft skills such as leadership and communication, are the main topics of discussion in this research. Christian religious education plays an important role in producing learners who are not only technically competent but also have strong moral integrity. This research is proven to have a positive impact on the transformation of students' personalities and support the development of professional skills relevant to the digital era.